The Creative Thinking Ability of MTs Students in Solving One Variable Linear Inequality Problems Viewed from Mathematics Anxiety - Maulida Aulia; Siswono, Tatag Yuli Eko; Harini, Novita Vindri (Universitas Negeri Surabaya, 2025)
This study aims to describe the creative thinking abilities of Madrasah Tsanawiyah (MTs) students in solving problems in the material of one variable linear related to the level of mathematical anxiety. The approach used was qualitative descriptive involving three students from class VIII of MTs Al-Ibrohimi Gresik who were selected by purposive sampling based on low, medium, and high levels of mathematical anxiety. The research instruments included a mathematical anxiety questionnaire, a mathematical creative thinking ability test, and interview guidelines. Based on the results of data analysis, students with low anxiety levels showed fulfillment of the four indicators of creative thinking, namely fluency, flexibility, originality, and elaboration so that they were classified in the category of very creative. Participants with moderate anxiety met two indicators, namely flexibility and elaboration, which indicated a sufficient level of creativity. Meanwhile, students with high anxiety only met one indicator, namely flexibility, and were classified as less creative. The results of this study show a tendency to decline the ability to think creatively along with the increasing level of students' mathematical anxiety in the process of solving mathematical problems.